High performance of the sodium‐ion conducting flexible polymer blend composite electrolytes for electrochemical double‐layer supercapacitor applications. Issue 5 (29th April 2022) - Sadiq, Mohd; Tanwar, Shweta; Raza, Mohammad Moeen Hasan; Aalam, Shah Masheerul; Sarvar, Mohd; Zulfequar, Mohammad; Sharma, A.L.; Ali, Javid
Abstract: Herein, we present the synthesis of a nanocomposite blend of polyvinyl alcohol (PVA), polyethylene glycol (PEG), sodium nitrate (NaNO3 ), and various weight percent of nanofillers, BaTiO3, using a simple standard solution casting technique. The prepared nanocomposites are characterized in detail via techniques such as X‐ray diffraction technique, field‐emission scanning microscope, FTIR, and Raman spectra for confirming the crystal structure, morphology, and chemical bond formation within the samples, respectively. The suitable ionic conductivity of prepared samples is in the range of 10 −4 –10 −8  S/cm at room temperature. Further, its maximum electrochemical stability window is ~4.1 V, and the ionic transference number is about 0.96 (15 wt%) at room temperature. The results associated with the optimized polymer nanocomposite motivated us to check its practical applicability for supercapacitors. The cyclic voltammetry of the fabricated cell based on optimized polymer as separator cum electrolyte appears as a distorted rectangle with no redox peaks. The cell charge storage mechanism is explored to be the electric double layer (EDLC) in nature. The maximum specific capacitance exhibited by the cell is nearly 4.4 F/g at a scan rate of 3 mV/s. The energy and power densities delivered by the same cell are equal to 27.7 W h kg −1 and 9972 W kg −1, respectively, which sustain for 100 cycles. The results of the designed cell reveal that both blend polymer composite electrolyte films and the composite electrode can be implemented to be used for EDLC supercapacitor.